Geomaritime-Based Marine and Fishery Economic Development in Maluku Islands - Atikah Nurhayati; Agus Heri Purnomo (Faculty of Geography, Universitas Gadjah Mada, 2017)
The design of national economic development should never ignore three important aspects, namely integration, and sustainably and local contexts. Insufficient comprehension over these three aspects has caused delays of economic progress in several regions like Maluku. This region is characterized with archipelagic geo-profile where marine and fisheries resources are abundant but economic progress is sluggish. To catch up with the achievement shown by regions in the western part of the country, there must by effective efforts done in Maluku. This research is aimed at analyzing the three aspects mentioned above as related to acceleration of marine and fisheries economic development based on the region’s maritime geo-profile. In line with it, primary and secondary data were applied on a SWOT Analytical Approach. Based on the analysis, it was concluded that acceleration of marine and fisheries economic development in Maluku can be carried out through both local and national policies focused on facilitating prospective economic players in making massive investment in the marine and fisheries sector. Among others, this should be done by improving the capacity of Maluku marine ports and directing them to be local economic transmiters, through more effective functions as hubs for ships carrying commodities and products for both national and international markets. This research found that in line with it, a pre-requirement that has to be advanced by the government is detailed zoning of marine and fisheries resources, which is supported by a legal umbrella.